Severe cases of local cytokine release syndrome (CRS); craniocervical edema soon after chimeric antigen T-cell (CAR-T) therapy - Nakamura, Naokazu; Jo, Tomoyasu; Arai, Yasuyuki; Kitawaki, Toshio; Nishikori, Momoko; Mizumoto, Chisaki; Kanda, Junya; Yamashita, Kouhei; Nagao, Miki; Takaori-Kondo, Akifumi (Oxford Medical Case Reports, 2025)
Craniocervical edema appears soon after chimeric antigen receptor T-cell (CAR-T) therapy in some cases. This phenomenon is often observed right after systemic cytokine release syndrome (CRS), and it is called local CRS (L-CRS). In severe cases, L-CRS causes airway obstruction and asphyxia, but it is not yet well known among hematologists. In this report, we present mild and severe cases of L-CRS. Tocilizumab might have limited efficacy against L-CRS, and early administration of corticosteroids can be important. We hope that this case report raises awareness of L-CRS as an acute-onset adverse event after CAR-T therapy.